Swimming Against the Tide: Primary Care Physicians’ Views on Deprescribing in Everyday Practice - Katharine Wallis; Abby Andrews; Michelle Henderson (2017)
PURPOSE Avoidable hospitalizations due to adverse drug events and high-risk prescribing are common in older people. Primary care physicians prescribe most on-going medicines. Deprescribing has long been essential to best prescribing practice. We sought to explore the views of primary care physicians on the barriers and facilitators to deprescribing in everyday practice to inform the development of an intervention to support safer prescribing. METHODS We used a snowball sampling technique to identify potential participants. Physicians were selected on the basis of years in practice, employment status, and practice setting, with an additional focus on information-rich participants. Twenty-four semistructured interviews were audio-recorded, transcribed verbatim, and analyzed to identify emergent themes. RESULTS Physicians described deprescribing as "swimming against the tide" of patient expectations, the medical culture of prescribing, and organizational constraints. They said deprescribing came with inherent risks for both themselves and patients and conveyed a sense of vulnerability in practice. The only incentive to deprescribing they identified was the duty to do what was right for the patient. Physicians recommended organizational changes to support safer prescribing, including targeted funding for annual medicines review, computer prompts, improved information flows between prescribers, improved access to expert advice and user-friendly decision support, increased availability of non-pharmaceutical therapies, and enhanced patient engagement in medicines management. CONCLUSIONS Interventions to support safer prescribing in everyday practice should consider the sociocultural, personal, relational, and organizational constraints on deprescribing. Regulations and policies should be designed to support physicians in practicing according to their professional ethical values.